Analyzing the Design and Implementation of Sustainable Energy Systems in Island Communities - Eze, Val Hyginus Udoka; Mwenyi, Joseph Mwenyi; Ukagwu, Kelechi John (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This review critically analyzes the design of sustainable energy systems implemented on islands and beyond. It emphasizes the importance of integrating renewable and non-renewable energy sources to enhance energy output in hybrid systems. Due to the Island's unique geographical and environmental characteristics, islands face distinct energy supply and sustainability challenges. The review examines different aspects of sustainable energy system design, such as renewable energy sources, energy storage solutions, grid integration, and policy frameworks. Hence, by synthesizing current research and case studies, this review aims to provide insights into effective strategies for designing sustainable energy systems that are specifically tailored to the needs and constraints of islands. This paper detailed the critical role of renewable energy sources such as solar, wind, hydro, and biomass in driving sustainability in island communities and urges energy stakeholders and policymakers to embrace their potential to effectively energize rural and underprivileged areas